Atlas of Neuromuscular Diseases A Practical Guideline - Feldman, Eva L.; Grisold, Wolfgang; Russell, James W.; Löscher, Wolfgang N. (Springer Vienna : Imprint: Springer, 2014)
This atlas presents a comprehensive outline of neuromuscular diseases, written by respected American and European authors. It discusses all aspects of neuromuscular disorders including cranial and spinal nerves, motor neuron diseases, nerve plexus, peripheral nerves, mono- and polyneuropathies, entrapment syndromes, neuromuscular junctions, and muscle disease. Each chapter is structured into the following sections: anatomy, symptoms, signs, pathogenesis, diagnosis and differential diagnosis, therapy and prognosis. The diagnostic tools in neuromuscular disease are explained and practical guidelines are offered on how to advance from symptoms to syndromes. The therapeutic options for each disease are also described. In this new edition, the structure of the chapters has been reorganized and chapters on principles of peripheral nerves, nerve pain, nerve surgery and rehabilitation have been added. The current trend of increased use of imaging techniques such as US and MRI in the diagnosis and follow-up of neuromuscular disorders is also reflected.